Solar irrigation in Yemen: Promising impacts several months post implementation - Darwish, Maram; Jovanovic, Nina; Kurdi, Sikandra; Yamauchi, Futoshi; SMEPS Communication and Advocacy Team (International Food Policy Research Institute, 2024)
Yemen faces one of the most significant humanitarian crises globally, with approximately 21.6 million people in need of some form of assistance, and an estimated 2.25 million children suffering from acute malnutrition. The situation is expected to worsen due to the country’s compromised food systems, local infrastructure, economy, and reliance on seasonal rainfall and groundwater sources for agricultural production. The ongoing conflicts, the great increase in prices of food commodities caused by the Russia-Ukraine war, and the unreliable access to diesel for pumping well water add yet another layer of complexity to an already dire situation, posing a great risk to country’s food security.